Buoyancy‐Driven Gradients for Biomaterial Fabrication and Tissue Engineering. Issue 17 (7th March 2019) - Li, Chunching; Ouyang, Liliang; Pence, Isaac J.; Moore, Axel C.; Lin, Yiyang; Winter, Charles W.; Armstrong, James P. K.; Stevens, Molly M.
Abstract: The controlled fabrication of gradient materials is becoming increasingly important as the next generation of tissue engineering seeks to produce inhomogeneous constructs with physiological complexity. Current strategies for fabricating gradient materials can require highly specialized materials or equipment and cannot be generally applied to the wide range of systems used for tissue engineering. Here, the fundamental physical principle of buoyancy is exploited as a generalized approach for generating materials bearing well‐defined compositional, mechanical, or biochemical gradients. Gradient formation is demonstrated across a range of different materials (e.g., polymers and hydrogels) and cargos (e.g., liposomes, nanoparticles, extracellular vesicles, macromolecules, and small molecules). As well as providing versatility, this buoyancy‐driven gradient approach also offers speed (<1 min) and simplicity (a single injection) using standard laboratory apparatus. Moreover, this technique is readily applied to a major target in complex tissue engineering: the osteochondral interface. A bone morphogenetic protein 2 gradient, presented across a gelatin methacryloyl hydrogel laden with human mesenchymal stem cells, is used to locally stimulate osteogenesis and mineralization in order to produce integrated osteochondral tissue constructs. The versatility and accessibility of this fabrication platform should ensure widespread applicability and provide opportunities to generate other gradient materials or interfacial tissues. Abstract : A versatile and tunable method for generating buoyancy‐driven gradients is used to fabricate controllable transitions in material composition and stiffness, as well as cargo gradients of nanoparticles, macromolecules, and proteins. The utility of this approach is demonstrated by patterning photo‐crosslinkable hydrogels with osteogenic growth factor gradients, which can locally differentiate human mesenchymal stem cells during osteochondral tissue engineering.